Perspectives on graduate employability attributes for management sciences graduates - Shivoro, R.S.; Shalyefu, R.K.; Kadhila, N. (South African Journal of Higher Education, 2018)
Higher education institutions need to take stock of the present scenario of graduate employability from both the employer and graduates’ perspectives, if they are to respond effectively to the needs of the labour market. Graduate employability is a concept that has gained popularity in the higher education sector in the world. The underlying assumption is that graduates need other attributes in addition to those skills needed in the subject-specific discipline. This paper provides an assessment of employers, graduates, and lecturers’ perceptions on graduate employability attributes for management sciences graduates in Namibia. Using a survey method of which questionnaires were administered to the three types of stakeholders, namely employers, lecturers and graduates. The study found a mismatch in responses between employers, lectures, and graduates regarding attributes that are important for the job market; those that are emphasized in curricula; and those that graduates need more training on. The argument presented by the paper is that mapping out the perceptions of stakeholders will enable higher education institutions to enhance graduate employability attributes needed by the labour market.